2011
DOI: 10.1503/cmaj.110407
|View full text |Cite
|
Sign up to set email alerts
|

Impact of remuneration and organizational factors on completing preventive manoeuvres in primary care practices

Abstract: P rimary care providers are increasingly in terested in ensuring that preventive health care be part of their work routines.1 This reorientation fits with the evidence that recommendations from family practitioners increase substantially the likelihood of patients undergoing preventive manoeuvres, 2 whereas the lack of such recommendations has been linked with patient noncompliance. 3,4 Studies evaluating adherence to recommended preventive care suggest that the most pervasive barriers rest with the organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 28 publications
3
44
1
Order By: Relevance
“…Findings of this study are in keeping with others reporting negative associations between panel size and cancer screening, 8,20 as well as with studies finding no associations with recommended chronic disease processes of care 20 and clinical outcome measures. 21 A possible explanation is that cancer-screening interventions are more time consuming because they necessitate a discussion of risks and benefits of screening and often the completion of a maneuver by the physician.…”
Section: Comparison With Other Studiessupporting
confidence: 91%
See 1 more Smart Citation
“…Findings of this study are in keeping with others reporting negative associations between panel size and cancer screening, 8,20 as well as with studies finding no associations with recommended chronic disease processes of care 20 and clinical outcome measures. 21 A possible explanation is that cancer-screening interventions are more time consuming because they necessitate a discussion of risks and benefits of screening and often the completion of a maneuver by the physician.…”
Section: Comparison With Other Studiessupporting
confidence: 91%
“…21 A possible explanation is that cancer-screening interventions are more time consuming because they necessitate a discussion of risks and benefits of screening and often the completion of a maneuver by the physician. Other time-consuming activities such as healthy lifestyle counseling and immunizations 8,20 have also been found to be negatively associated with higher panel sizes.The literature shows that primary care physicians carrying larger panel sizes may be more likely to refer complex patients to specialists, who would then be more likely to adhere to guidelines.22 Surprisingly, we found the likelihood of undergoing an echocardiogram within 1 year of a congestive heart failure diagnosis showed a positive association with panel size. From our data, we are unable to determine whether higher rates of referral to specialists, greater experience and expertise, or both could have contributed to this pattern.…”
mentioning
confidence: 99%
“…Our findings are consistent with cross-sectional studies from Ontario showing that patients who saw feefor-service physicians had the largest gaps in diabetes care 16 but that little of the difference in preventive screening could be attributed to the type of physician payment. 29 Our study builds on the longitudinal analysis by Kralj and Kantarevic, 30 who found that physicians who transitioned from feefor-service payment to capitation were 7% to 10% more likely to achieve cancer screening targets than those remaining in fee-for-service practice; however, in contrast to our study, theirs was a physician-level analysis and did not assess the relative influence of team-based care. Evidence from the US is mixed, whereby some studies have shown that practices that adopted components of patientcentred medical homes were more likely to provide better preventive services 11,[31][32][33][34] and chronic disease care, 11,33,34 whereas other studies showed that the rate of improvement in quality of care was no greater in patient-centred medical homes than in comparison practices.…”
Section: Discussionmentioning
confidence: 89%
“…27 Organizational and patient factors may also have influenced the impact of the incentives. Practices with electronic reminder systems have been shown to provide superior preventive care, 28 yet only 66% of primary care physicians in Ontario reported using electronic medical records and only 37% said they could easily generate a list of patients due for preventive care. 29 Cervical and breast cancer screening rates remained relatively stable over the last decade, as they have in the United States 30 and the United Kingdom, 31 which may relate to some patients making an informed choice not to be screened.…”
Section: Discussionmentioning
confidence: 99%